The Benefits of High-Resistant Starch and Beta-Carotene Snack in Ameliorating Atherogenic Index and Inflammation in Obesity - Sunarti, Sunarti; Rubi, Dianandha Septiana; Pramana, Abrory Agus Cahya; Huriyati, Emy; Santoso, Umar (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: In obesity, lipid abnormalities may be related to the higher risk of cardiovascular diseases associated with increased oxidation of lipids and inflammation. Resistant starch and beta-carotene reduce atherosclerosis risk related to low-grade inflammation and oxidative stress in obesity. AIM: This study aimed to evaluate the benefits of a snack containing high-resistant starch and beta-carotene in improving the atherogenic index of plasma (AIP) and inflammation in obesity. METHODS: This study used a single-blinded and randomized controlled design. Fifty subjects received 42 g of snacks per day for 6 weeks, either tested snacks or standard snacks. Anthropometry, body composition, lipid profile, tumor necrosis factor-alpha (TNF-α), and oxidized low-density lipoprotein (ox-LDL) were measured before and after intervention. RESULTS: The snack containing high-resistant starch and beta-carotene significantly decreased LDL, AIP, and TNF-α (p < 0.05). Positive correlations were found between AIP and triglycerides in both snacks (p < 0.05), LDL or TNF-α in the standard snack (p < 0.05), and TNF-α and ox-LDL in both snacks (p < 0.05). A negative correlation was found between AIP and HDL in both snacks (p < 0.05). CONCLUSIONS: A snack containing high-resistant starch and beta-carotene reduced AIP and inflammation by preventing LDL oxidation.